A study of trade union effectiveness in Malaysia - Eden, Dzulzalani (Institute of Labour Market Information and Analysis, 2017)
This study aimed to assess the role of trade unions in the Malaysian industrial relations system. This study has identified many important results from the analysis carried out in the aspects of trade unions effectiveness and the perception of the trade union members on the implementation of the Trans-Pacific Partnership Agreement (TPPA). In addition, the study has also performed benchmarking exercise to determine the current state of trade unionism in Malaysia in comparison with ten other countries in the Asia Pacific, Europe and America regions.